Argumentative procedures in E-commerce environments - Novais, Paulo (2003)
The use of agent's technology in electronic commerce environments leads to the necessity to introduce some sort of formal attitude in the processes of software development and analysis. Logic programming and specially extended logic programming provides a powerful tool for achieving such goal; i.e., besides being mathematically correct it makes the prototyping phase easier. However, although no simple methodology had yet been stated to address the complexity present in this approach, it not only addresses problems of architecture development and analysis, but also looks at problems of knowledge representation and reasoning, and machine learning. Such a framework will follow the Experience-Based Mediator agent paradigm particularly suited to take into account the argumentation schemes that are inherent to any electronic commerce deal.